Leather composite material capable of continuously releasing negative ions and preparation method

By using polyvinyl chloride resin powder surface slurry with nano tourmaline powder and other components in the automotive seat cushion material, a leather composite material that can sustainably release negative ions is prepared, which solves the shortcomings of existing materials in terms of comfort, durability, environmental adaptability, health and environmental protection, and achieves the effect of improving air quality and extending service life.

CN119593223APending Publication Date: 2025-03-11GUANGZHOU HIGHTEEN PLASTICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411919753.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing automotive seat cushion materials have shortcomings in terms of comfort, durability, environmental adaptability and health and environmental protection, especially the lack of negative ion release function of synthetic leather materials, which limits its potential to improve the air quality in the car.

Method used

A polyvinyl chloride resin powder surface slurry containing nano tourmaline powder, epoxy soybean oil, polydimethylsiloxane and other components is used to prepare a leather composite material that can sustainably release negative ions through specific chemical additives and nanomaterials.

Benefits of technology

The material not only continuously releases negative ions and improves air quality, but also has enhanced wear and yellowing resistance, extends the service life of the product and provides health benefits of antioxidant and UV protection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a leather composite material capable of continuously releasing negative ions and a preparation method, and belongs to the technical field of leathes.The composite material comprises a polyvinyl chloride surface layer, a foaming layer and a base cloth layer, continuous release of the negative ions is achieved through a specific preparation technology, the polyvinyl chloride surface layer is made of polyvinyl chloride resin powder, nano tourmaline powder and other raw materials, and the base cloth layer is made of nano tourmaline powder; the preparation method comprises a series of mixing and drying steps. The foaming layer is prepared from polyvinyl chloride resin powder, azodiisobutyronitrile and other raw materials through high-speed stirring and drying; the base cloth layer is leather base cloth and is formed by laminating and drying. Compared with the prior art, the composite material disclosed by the invention not only has excellent mechanical properties and durability, but also can effectively release negative ions and improve air quality by adding the nano tourmaline powder, and is especially suitable for the fields of automotive interior materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of leather, and in particular to a leather composite material capable of sustainably releasing negative ions and a preparation method thereof. Background Art

[0002] With the rapid development of the automobile industry, people have higher and higher requirements for automobile interior materials, especially car seat cushions. Car seat cushions not only need to provide a comfortable riding experience, but also have good durability, aesthetics and environmental friendliness. The car seat cushion materials currently on the market mainly include natural leather, synthetic leather and other engineering plastics.

[0003] Although natural leather has advantages in terms of comfort and texture, it has problems such as high cost, limited resources and environmental pollution during the production process. Although synthetic leather simulates the appearance and performance of natural leather to a certain extent, it often has deficiencies in wear resistance, aging resistance and environmental adaptability. In addition, synthetic leather materials in the prior art may not have or only have limited negative ion release function, which limits its potential in improving the air quality in the car.

[0004] Although other materials such as engineering plastics have advantages in terms of cost and durability, they usually lack the texture and comfort of leather, and are also limited in terms of aesthetics and environmental friendliness. At the same time, these materials may release volatile organic compounds in long-term use, posing a potential threat to the air quality in the car and the health of passengers.

[0005] In view of this, the demand for technological innovation of automotive seat cushion materials is mainly focused on improving the comfort, durability, environmental adaptability and health and environmental protection of the materials. In particular, the development of a synthetic leather composite material that can continuously release negative ions and improve air quality is of great significance to improving the functionality and riding experience of automotive interiors.

[0006] China's invention patent CN107899588B discloses a negative ion ecological artificial leather and its preparation method, the artificial leather includes a polyvinyl chloride surface layer, a foaming layer and a base fabric layer, the polyvinyl chloride surface layer is formed by drying the polyvinyl chloride surface layer slurry at 160-180°C; the base fabric layer is made of a leather base fabric, and the leather base fabric is pretreated with an antibacterial and wrinkle-proof finishing agent. The artificial leather described in the invention has excellent mechanical properties and processing properties, low cost, low volatile organic compound content, acid and alkali resistance, and is widely used in shoes, furniture, various indoor and outdoor decorations, and aircraft, automobile, and ship decorations. However, the long-term environmental stability and durability of the artificial leather prepared by the invention may be poor in practical applications. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to develop a new type of leather composite material that can sustainably release negative ions, which can not only provide health benefits of improving air quality, but also provide enhanced wear resistance and yellowing resistance while maintaining the leather texture.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a leather composite material capable of continuously releasing negative ions is as follows: Step 1, preparation of surface slurry: take a formulated amount of polyvinyl chloride resin powder, mix it with nano tourmaline powder and calcium stearate at 70-90°C and 110-130r / min for 10-20 minutes; add epoxy soybean oil, polydimethylsiloxane, dibutyl adipate, sodium tripolyphosphate, di-tert-butyl-p-cresol, mix it at 60-70°C and 100-300r / min for 40-80 minutes; finally add zinc oxide, tea tree oil and pigment, mix it at 30-50°C and 1000-1500r / min for 40-60 minutes; Step 2, preparing a foaming slurry: adding polyvinyl chloride resin powder, azobisisobutyronitrile, polyethylene terephthalate, a foaming agent, and polyhexamethylene biguanide into a high-speed disperser for stirring, introducing air during the stirring process, the stirring time is 30 to 50 minutes, and the speed is 1000 to 1500 r / min; Step 3, forming: evenly apply the surface layer slurry on the release paper, and dry it at 150-180°C to form a surface layer; evenly apply the foaming slurry on the surface layer, and dry it at 180-190°C to form a foaming layer; laminate the leather base fabric on the foaming layer, and dry it at 170-190°C; remove the release paper, roll-coat the finishing agent on the surface layer, and dry it at 50-70°C to obtain a leather composite material.

[0009] The weight proportions of the substances in step 1 are 120-180 parts of polyvinyl chloride resin powder, 12-18 parts of nano-tourmaline powder, 3-5 parts of calcium stearate, 35-45 parts of epoxy soybean oil, 1-3 parts of polydimethylsiloxane, 8-12 parts of dibutyl adipate, 1.2-1.8 parts of sodium tripolyphosphate, 0.5-1 parts of di-tert-butyl-p-cresol, 0.5-2 parts of zinc oxide, 2-4 parts of tea tree oil, and 1-3 parts of pigment.

[0010] The weight proportions of the substances in step 2 are 100-140 parts of polyvinyl chloride resin powder, 40-60 parts of azobisisobutyronitrile, 10-15 parts of polyethylene terephthalate, 2-4 parts of foaming agent, and 1-3 parts of polyhexamethylene biguanide.

[0011] The finishing agent is composed of the following materials in parts by weight: 20-40 parts of waterborne polyurethane, 4-8 parts of functional agent, 3-5 parts of carboxymethyl cellulose, 0.5-2 parts of diethanolamine, 0.5-2 parts of dimethyl silicone oil, 2-4 parts of nano-alumina, and 0.5-2 parts of sodium bicarbonate.

[0012] The thickness of the surface layer is 0.1-0.3 mm; the thickness of the foaming layer is 0.5-2 mm; and the roller coating thickness of the finishing agent is 0.01-0.03 mm.

[0013] The preparation method of the functional agent is as follows, in parts by weight: S1. Mix 1-2 parts of ammonium borate and 8-12 parts of M-aminophenyltrimethoxysilane in 20-40 parts of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 60-80°C and keep warm for 0.5-2 hours, then heat to 120-140°C and keep warm for 0.5-1 hour, and continue to heat to 130-150°C and keep warm for 1-2 hours; add 0.3-0.8 parts of 2,5-dihydroxyacetophenone and 0.02-0.06 parts of tin tetrachloride in sequence, continue to keep warm and stir for 4-6 hours; remove the solvent after cooling, and dry at 50-70°C for 5-10 hours to obtain a pretreatment agent; mix 0.4-0.8 parts of the pretreatment agent and 1-1.5 parts of carnauba wax in 8-12 parts of toluene, heat to 50-70°C, and stir for 0.5-2 hours; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.5-1 part of zirconium chloride in 70-90 parts of anhydrous ethanol, and dispersing by ultrasonic; adding 4-6 parts of 1-3 mol / L sodium hydroxide aqueous solution, reacting for 1-5 hours under stirring, and then pouring the mixed solution into a reactor, reacting for 5-15 hours at 160-200°C; cooling to room temperature, centrifuging and washing 1-3 times, and vacuum drying at 40-60°C for 5-10 hours to obtain a solid compound; adding 0.05-0.2 parts of the solid compound to 15-25 parts of 8-12 wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.5-1 part of tea polyphenols to 50-70 parts of 40-70 wt% ethanol aqueous solution; dispersing by ultrasonic, and adding 0.4-0.6 mol / L phosphoric acid to adjust the pH of the mixture; stirring and reacting at 40-60°C for 5-15 hours, washing with anhydrous ethanol 1-3 times after centrifugation, and drying at 40-60°C for 4-10 hours to obtain an additive; S3, uniformly mixing the prepared modifier and additive to obtain a functional agent.

[0014] The pH of the mixture is adjusted to 5-6.

[0015] The power of the ultrasonic dispersion is independently 150-300 W, the frequency is independently 20-60 kHz, and the time is independently 20-50 minutes.

[0016] The modifier and the additive are mixed evenly in a weight ratio of 1-3:0.5-1.

[0017] In the present invention, the functions of each substance are as follows: Polyvinyl chloride resin powder is used as the basic material of the surface slurry and provides the main structure of the leather composite material.

[0018] Nano tourmaline powder is used to generate negative ions and improve the ambient air quality.

[0019] Calcium stearate acts as a lubricant to improve the fluidity and processing properties of resin powder.

[0020] Epoxidized soybean oil, polydimethylsiloxane and dibutyl adipate are used as plasticizers to increase the flexibility and elasticity of the material.

[0021] Sodium tripolyphosphate is used as a stabilizer to improve the thermal stability of the material.

[0022] Di-tert-butyl-p-cresol acts as an antioxidant to extend the service life of the material.

[0023] Zinc oxide, tea tree oil, pigments Zinc oxide acts as an active agent, tea tree oil provides natural preservative properties, and pigments are used for coloring.

[0024] Azobisisobutyronitrile, as a component of the foaming agent, affects the formation of the foaming layer.

[0025] Polyethylene terephthalate, as one of the raw materials of the foaming layer, provides specific physical properties.

[0026] Polyhexamethylene biguanide acts as a foaming stabilizer to control the foam structure.

[0027] Carboxymethyl cellulose, diethanolamine, dimethyl silicone oil, nano-alumina, and sodium bicarbonate are used as finishing agents to improve the surface properties and feel of composite materials.

[0028] Ammonium borate is used as a reactant in the preparation of the functional agent and participates in the formation of the pretreatment agent.

[0029] M-aminophenyltrimethoxysilane is the main component of the functional agent, providing wear resistance and anti-yellowing properties.

[0030] 2,5-Dihydroxyacetophenone, as a reactant, participates in the chemical reaction of forming the pretreatment agent, and tin tetrachloride, as a catalyst, promotes the reaction.

[0031] As part of the modifier, carnauba wax increases the gloss and improves the feel of the material.

[0032] Zirconium chloride is used as a reactant in the preparation of additives and participates in the formation of solid compounds.

[0033] Tea polyphenols enhance the material's yellowing resistance and wear resistance.

[0034] Phosphoric acid is used to adjust the pH value of the additive solution, affecting the reaction conditions and product properties.

[0035] These substances work together to form a leather composite material with sustainable release of negative ions, excellent wear resistance and yellowing resistance.

[0036] Compared with the prior art, it has the following beneficial effects: 1) The leather composite material of the present invention can effectively release negative ions by adding nano tourmaline powder, which has significant advantages in improving air quality and creating a healthy environment, and provides users with additional environmental improvement effects.

[0037] 2) The present invention adds specific chemical additives and nanomaterials to the surface slurry, and the composite material of the present invention exhibits better wear resistance and yellowing resistance. This allows the material to maintain the stability of appearance and structure during long-term use, extending the service life of the product.

[0038] 3) The composite material of the present invention not only provides environmentally friendly anti-yellowing protection, but also may bring health benefits such as antioxidant and UV protection, enhancing the environmental attributes of the material and the care for the health of the user. DETAILED DESCRIPTION

[0039] Main sources of substances: Polyvinyl chloride resin powder: Dongguan Huaqing Plastic Co., Ltd., brand: S-80.

[0040] Nano tourmaline powder: Shijiazhuang Chenghe New Material Technology Co., Ltd., item number: CH-dqs.

[0041] Epoxidized soybean oil: Jinan Luying Chemical Co., Ltd., product number: 104654.

[0042] Polydimethylsiloxane: Shandong Yousuo Chemical Technology Co., Ltd., model: PMX-200.

[0043] Polyethylene terephthalate: Shanghai Gaoming Chemical Co., Ltd., item number: 65156714.

[0044] Polyhexamethylene biguanide: Shandong Shengrui Chemical Technology Co., Ltd., product number: SR-22.

[0045] Waterborne polyurethane: Anhui Feimiao Chemical Co., Ltd., model: FS-7.

[0046] Nano-alumina: Nanjing Paket New Materials Co., Ltd., product number: PAT.

[0047] Foaming agent: Shanghai Yunhe Material Technology Co., Ltd., product model: 920DU40.

[0048] Leather fabric: Yingde Hongli Leather Co., Ltd., main component: polyester, weight: 120g / m 2 .

[0049] Pigment: Shenzhen Yingcai Pigment Technology Co., Ltd., item number: 2018010030.

[0050] Phenyltrimethoxysilane: CAS number: 2996-92-1.

[0051] 3-[Tris(1-methylethoxy)silyl]propyl methacrylate: CAS number: 80750-05-6.

[0052] 1,4-Bis(trimethylsilyloxy)benzene: CAS number: 90162-40-6.

[0053] M-Aminophenyltrimethoxysilane: CAS number: 33976-43-1.

[0054] Ethyl 3,4-dihydroxybenzoate: CAS number: 3943-89-3.

[0055] Methyl gallate: CAS number: 99-24-1.

[0056] Tea polyphenols: CAS number: 84650-60-2.

[0057] The design idea of ​​the present invention is to create a leather composite material that can release negative ions sustainably. The material not only has excellent mechanical properties and durability, but also gives the material additional environmental and health benefits through specific functional agents. This goal is achieved by carefully selecting and proportioning various raw materials, including polyvinyl chloride resin powder, nano tourmaline powder, etc., to build the basic structure of the composite material. The key innovation lies in the introduction of the functional agent, which is prepared through a specific chemical synthesis path, which not only enhances the wear resistance and yellowing resistance of the material, but also provides antioxidant and UV protection capabilities through the addition of active substances such as tea polyphenols. In addition, the formula design of the finishing agent takes into account the post-processing requirements of the material to ensure the quality and performance of the finished product. Overall, the design idea of ​​the present invention is to develop a new leather composite material that is high-performance, environmentally friendly, and has health benefits through the deep integration of materials science and chemical engineering. Example 1

[0058] A method for preparing a leather composite material capable of continuously releasing negative ions is as follows: Step 1, preparation of surface slurry: take 150g of polyvinyl chloride resin powder in the formula, mix it with 15g of nano tourmaline powder and 4g of calcium stearate at 80°C and 120r / min for 15 minutes; add 40g of epoxy soybean oil, 2g of polydimethylsiloxane, 10g of dibutyl adipate, 1.5g of sodium tripolyphosphate, and 0.8g of di-tert-butyl-p-cresol, and mix it at 65°C and 200r / min for 60 minutes; finally, add 1g of zinc oxide, 3g of tea tree oil, and 1.5g of pigment, and mix it at 40°C and 1200r / min for 50 minutes; Step 2, preparing a foaming slurry: adding 120g of polyvinyl chloride resin powder, 50g of azobisisobutyronitrile, 12g of polyethylene terephthalate, 3g of a foaming agent, and 2g of polyhexamethylene biguanide into a high-speed disperser for stirring, introducing air during the stirring process, and stirring for 40 minutes at a speed of 1200r / min; Step 3, molding: evenly apply the surface layer slurry on the release paper, and dry it at 170°C to form a surface layer with a thickness of 0.2mm; evenly apply the foaming slurry on the surface layer, and dry it at 185°C to form a foaming layer with a thickness of 1mm; attach the leather base cloth to the foaming layer and dry it at 180°C; remove the release paper, and roll-coat the surface layer with a finishing agent, wherein the finishing agent is composed of 30g water-based polyurethane, 6g functional agent, 4g carboxymethyl cellulose, 1g diethanolamine, 1g dimethyl silicone oil, 3g nano-alumina, and 1g sodium bicarbonate, and is dried at 60°C. The roller coating thickness of the finishing agent is 0.02mm to obtain a leather composite material.

[0059] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of M-aminophenyltrimethoxysilane in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting under stirring for 3 hours, then pouring the mixed solution into a reactor, reacting at 180°C for 10 hours; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g tea polyphenols to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, centrifuging and washing 3 times with anhydrous ethanol, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent. Example 2

[0060] The method for preparing a leather composite material capable of continuously releasing negative ions is substantially the same as that in Example 1, the only difference being that the method for preparing the functional agent is different.

[0061] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of 1,4-bis(trimethylsilyloxy)benzene in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting under stirring for 3 hours, then pouring the mixed solution into a reactor, reacting at 180°C for 10 hours; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g tea polyphenols to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, centrifuging and washing 3 times with anhydrous ethanol, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent. Example 3

[0062] The method for preparing a leather composite material capable of continuously releasing negative ions is substantially the same as that in Example 1, the only difference being that the method for preparing the functional agent is different.

[0063] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of 3-[tri(1-methylethoxy)silyl]propyl methacrylate in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting under stirring for 3 hours, then pouring the mixed solution into a reactor, reacting at 180°C for 10 hours; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g tea polyphenols to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, centrifuging and washing 3 times with anhydrous ethanol, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent. Example 4

[0064] The method for preparing a leather composite material capable of continuously releasing negative ions is substantially the same as that in Example 1, the only difference being that the method for preparing the functional agent is different.

[0065] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of phenyltrimethoxysilane in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting under stirring for 3 hours, then pouring the mixed solution into a reactor, reacting at 180°C for 10 hours; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g tea polyphenols to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, centrifuging and washing 3 times with anhydrous ethanol, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent. Example 5

[0066] The method for preparing a leather composite material capable of continuously releasing negative ions is substantially the same as that in Example 1, the only difference being that the method for preparing the functional agent is different.

[0067] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of M-aminophenyltrimethoxysilane in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting for 3 hours under stirring, then pouring the mixed solution into a reactor, reacting for 10 hours at 180°C; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g methyl gallate to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added dropwise to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, washing 3 times with anhydrous ethanol after centrifugation, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent. Example 6

[0068] The method for preparing a leather composite material capable of continuously releasing negative ions is substantially the same as that in Example 1, the only difference being that the method for preparing the functional agent is different.

[0069] The preparation method of the functional agent is as follows: S1. Mix 1.5 g of ammonium borate and 10 g of M-aminophenyltrimethoxysilane in 30 g of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 70°C and keep warm for 1 hour, then heat to 130°C and keep warm for 0.8 hour, and continue to heat to 140°C and keep warm for 1.5 hours; add 0.5 g of 2,5-dihydroxyacetophenone and 0.04 g of tin tetrachloride in sequence, continue to keep warm and stir for 5 hours; remove the solvent after cooling, and dry at 60°C for 8 hours to obtain a pretreatment agent; mix 0.6 g of the pretreatment agent and 1.2 g of carnauba wax in 10 g of toluene, heat to 60°C, and stir for 1 hour; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.8g zirconium chloride in 80g anhydrous ethanol, ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 30 minutes; adding 5g 2mol / L sodium hydroxide aqueous solution, reacting for 3 hours under stirring conditions, and then pouring the mixed solution into a reactor, reacting for 10 hours at 180°C; cooling to room temperature, centrifuging and washing 3 times, and vacuum drying at 50°C for 8 hours to obtain a solid compound; adding 0.1g of the solid compound to 20g 10wt% ethanol aqueous solution, and then adding an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.8g 3,4-dihydroxybenzoic acid ethyl ester to 60g 50wt% ethanol aqueous solution; ultrasonically dispersing, the power of the ultrasonic dispersion is 200W, the frequency is 40kHz, and the time is 40 minutes, and 0.5mol / L phosphoric acid is added dropwise to adjust the pH of the mixture to 5; stirring and reacting at 50°C for 10 hours, centrifuging and washing 3 times with anhydrous ethanol, and drying at 50°C for 7 hours to obtain an additive; S3. The prepared modifier and additive are uniformly mixed in a weight ratio of 2:0.8 to obtain a functional agent.

[0070] Comparative Example 1 A method for preparing a leather composite material capable of continuously releasing negative ions is as follows: Step 1, preparation of surface slurry: take 150g polyvinyl chloride resin powder in the formula, mix it with 15g nano tourmaline powder and 4g calcium stearate at 80°C and 120r / min for 15 minutes; add 40g epoxy soybean oil, 2g polydimethylsiloxane, 10g dibutyl adipate, 1.5g sodium tripolyphosphate, 0.8g di-tert-butyl-p-cresol, and mix it at 65°C and 200r / min for 60 minutes; finally, add 1g zinc oxide, 3g tea tree oil, and 1.5g pigment, and mix it at 40°C and 1200r / min for 50 minutes; Step 2, preparing a foaming slurry: adding 120g of polyvinyl chloride resin powder, 50g of azobisisobutyronitrile, 12g of polyethylene terephthalate, 3g of a foaming agent, and 2g of polyhexamethylene biguanide into a high-speed disperser for stirring, introducing air during the stirring process, and stirring for 40 minutes at a speed of 1200r / min; Step 3, molding: evenly apply the surface layer slurry on the release paper, and dry it at 170°C to form a surface layer with a thickness of 0.2mm; evenly apply the foaming slurry on the surface layer, and dry it at 185°C to form a foaming layer with a thickness of 1mm; attach the leather base cloth to the foaming layer and dry it at 180°C; remove the release paper, and roll-coat the surface layer with a finishing agent, wherein the finishing agent is composed of 30g aqueous polyurethane, 4g carboxymethyl cellulose, 1g diethanolamine, 1g dimethyl silicone oil, 3g nano-alumina, and 1g sodium bicarbonate, and is dried at 60°C. The roller coating thickness of the finishing agent is 0.02mm to obtain a leather composite material.

[0071] Test Example 1 Wear test According to ASTM standard D3884, an H-22 wear wheel was selected and a unidirectional load of 750 grams was applied.

[0072] The wear wheel reciprocates on the material surface to simulate the friction conditions that may be encountered in actual use.

[0073] Judging criteria: Level 1: After 500 wear cycles, the surface of the material is worn flat or damaged; Level 2: After 1,000 wear cycles, the surface of the material begins to be worn flat or damaged; Level 3: The material surface shows signs of wear after 1,500 wear cycles; Level 4: After 2000 wear cycles, the surface of the material is worn flat or damaged; Level 5: After 2500 or more wear cycles, the texture of the material surface remains intact and there is no obvious damage.

[0074] The test results are shown in Table 1.

[0075] Table 1 Experimental protocol Wear resistance grade Example 1 Level 5 Example 2 Level 4 Example 3 Level 4 Example 4 Level 4 Example 5 Level 4 Example 6 Level 4 Comparative Example 1 Level 3 Test Example 2 Yellowing resistance test First, the synthetic leather material was made into uniform test pieces with a size of 50mm×20mm. One of the pieces was retained as an unexposed control group. The remaining test pieces were placed in a weathering test chamber and continuously irradiated with ultraviolet light with a total power of 400W for a period of 24 hours. During the test, the test pieces were kept at a fixed distance of 30 cm from the light source and accelerated aging simulation was performed at a controlled ambient temperature of 60°C. After the test, the test pieces were taken out and naturally cooled at room temperature for at least 10 minutes so that the temperature dropped to the ambient level. Subsequently, the color changes of these light-treated test pieces were observed, and the color differences were compared and analyzed with the control group that was not affected by light using a neutral gray color card. The test results are shown in Table 2.

[0076] Table 2 Experimental protocol Yellowing resistance grade Example 1 5 Example 2 5 Example 3 4 Example 4 4.5 Example 5 4.5 Example 6 4 Comparative Example 1 3 It can be seen from test examples 1 and 2 that the leather composite material obtained in Example 1 of the present invention has the best wear resistance and yellowing resistance.

[0077] The molecular binding of M-aminophenyltrimethoxysilane with ammonium borate is a complex process involving multiple interactions. First, the amino group in M-aminophenyltrimethoxysilane is a nucleophilic site that can form a coordination bond with the boron atom in ammonium borate. Under heating conditions, this coordination effect is enhanced because the increase in temperature increases the kinetic energy of the molecules and promotes the occurrence of effective collisions, which is conducive to the formation of coordination bonds. At the same time, stirring provides uniformity of physical mixing and ensures sufficient contact between the reactants. As the reaction proceeds, the benzene ring structure of M-aminophenyltrimethoxysilane may form non-covalent interactions with other molecules, increasing the intermolecular stacking and stability. In addition, the trimethoxysilane group may form a strong interaction with the inorganic or organic matrix through the silicon-oxygen bond, enhancing the intermolecular connection. Ultimately, this intermolecular coordination and interaction provides the composite with enhanced cohesion and crosslinking density, which manifests as better wear resistance and yellowing resistance on a macroscopic level. This molecular-level binding and action mechanism provides a solid theoretical basis for the preparation of high-performance functional agents. In contrast, although the silane coupling agents used in Examples 2, 3 and 4 also contain silicon-oxygen bonds, they contribute less to the reaction activity and polarity improvement due to the lack of amino groups, and are therefore inferior to Example 1 in terms of wear resistance and yellowing resistance.

[0078] Tea polyphenols, as a natural compound rich in polyphenolic hydroxyl groups, have multiple hydroxyl functional groups in their molecular structure that provide them with strong antioxidant properties and ultraviolet light absorption capabilities. In Example 1 of the present invention, the introduction of tea polyphenols provides an additional protection mechanism for leather composite materials at the molecular level. First, the antioxidant properties of tea polyphenols can neutralize the free radicals that may be generated by the material under light or thermal stress, thereby slowing down the oxidative degradation process of the material and maintaining the stability and integrity of its structure, which helps to improve the yellowing resistance of the material. Secondly, the ultraviolet light absorption characteristics of tea polyphenols can block the direct effect of ultraviolet rays on the material to a certain extent, reduce the photochemical degradation and yellowing reaction caused by ultraviolet rays, thereby protecting the stability of the color of the material surface. In addition, the hydroxyl groups in the tea polyphenol molecules can form hydrogen bonds with zirconium-containing compounds, enhance the interaction between molecules, and help to form a more uniform and stable protective layer on the material surface. This protective layer can not only improve the mechanical strength and wear resistance of the material, but also resist the erosion of the material by external factors to a certain extent.

[0079] In contrast, although methyl gallate and ethyl 3,4-dihydroxybenzoate also have certain antioxidant properties, the number and properties of the functional groups in their molecules may not be comparable to those of tea polyphenols, so they are not as good as tea polyphenols in terms of wear resistance and yellowing resistance.

Claims

1. A method for preparing a leather composite material capable of continuously releasing negative ions, characterized in that: Here’s how: Step 1, preparation of surface slurry: take a formulated amount of polyvinyl chloride resin powder, mix it with nano tourmaline powder and calcium stearate at 70-90°C and 110-130r / min for 10-20 minutes; add epoxy soybean oil, polydimethylsiloxane, dibutyl adipate, sodium tripolyphosphate, di-tert-butyl-p-cresol, mix it at 60-70°C and 100-300r / min for 40-80 minutes; finally add zinc oxide, tea tree oil and pigment, mix it at 30-50°C and 1000-1500r / min for 40-60 minutes; Step 2, preparing a foaming slurry: adding polyvinyl chloride resin powder, azobisisobutyronitrile, polyethylene terephthalate, a foaming agent, and polyhexamethylene biguanide into a high-speed disperser for stirring, introducing air during the stirring process, the stirring time is 30 to 50 minutes, and the speed is 1000 to 1500 r / min; Step 3, forming: evenly apply the surface layer slurry on the release paper, and dry it at 150-180°C to form a surface layer; evenly apply the foaming slurry on the surface layer, and dry it at 180-190°C to form a foaming layer; The leather base fabric is laminated on the foaming layer and dried at 170-190°C; the release paper is removed, a finishing agent is roller-coated on the surface layer, and the leather composite material is obtained by drying at 50-70°C.

2. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 1, characterized in that: The weight proportions of the substances in step 1 are 120-180 parts of polyvinyl chloride resin powder, 12-18 parts of nano-tourmaline powder, 3-5 parts of calcium stearate, 35-45 parts of epoxy soybean oil, 1-3 parts of polydimethylsiloxane, 8-12 parts of dibutyl adipate, 1.2-1.8 parts of sodium tripolyphosphate, 0.5-1 parts of di-tert-butyl-p-cresol, 0.5-2 parts of zinc oxide, 2-4 parts of tea tree oil, and 1-3 parts of pigment.

3. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 1, characterized in that: The weight proportions of the substances in step 2 are 100-140 parts of polyvinyl chloride resin powder, 40-60 parts of azobisisobutyronitrile, 10-15 parts of polyethylene terephthalate, 2-4 parts of foaming agent, and 1-3 parts of polyhexamethylene biguanide.

4. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 1, characterized in that: The finishing agent is composed of the following materials in parts by weight: 20-40 parts of waterborne polyurethane, 4-8 parts of functional agent, 3-5 parts of carboxymethyl cellulose, 0.5-2 parts of diethanolamine, 0.5-2 parts of dimethyl silicone oil, 2-4 parts of nano-alumina, and 0.5-2 parts of sodium bicarbonate.

5. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 1, characterized in that: The thickness of the surface layer is 0.1-0.3 mm; the thickness of the foaming layer is 0.5-2 mm; and the roller coating thickness of the finishing agent is 0.01-0.03 mm.

6. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 3, characterized in that: The preparation method of the functional agent is as follows, in parts by weight: S1. Mix 1-2 parts of ammonium borate and 8-12 parts of M-aminophenyltrimethoxysilane in 20-40 parts of diethylene glycol monoisobutyl ether, protect with nitrogen, and stir continuously; first heat to 60-80°C and keep warm for 0.5-2 hours, then heat to 120-140°C and keep warm for 0.5-1 hour, and continue to heat to 130-150°C and keep warm for 1-2 hours; add 0.3-0.8 parts of 2,5-dihydroxyacetophenone and 0.02-0.06 parts of tin tetrachloride in sequence, continue to keep warm and stir for 4-6 hours; remove the solvent after cooling, and dry at 50-70°C for 5-10 hours to obtain a pretreatment agent; mix 0.4-0.8 parts of the pretreatment agent and 1-1.5 parts of carnauba wax in 8-12 parts of toluene, heat to 50-70°C, and stir for 0.5-2 hours; remove the solvent after cooling to obtain a modifier; S2, dissolving 0.5-1 part of zirconium chloride in 70-90 parts of anhydrous ethanol, and dispersing by ultrasonication; Add 4 to 6 parts of 1 to 3 mol / L sodium hydroxide aqueous solution, react for 1 to 5 hours under stirring conditions, then pour the mixed solution into a reactor, react for 5 to 15 hours at 160 to 200° C.; after cooling to room temperature, centrifuge and wash 1 to 3 times, and vacuum dry at 40 to 60° C. for 5 to 10 hours to obtain a solid compound; add 0.05 to 0.2 parts of the solid compound to 15 to 25 parts of 8 to 12 wt% ethanol aqueous solution, and then add an ethanol-based treatment liquid; the ethanol-based treatment liquid is prepared by adding 0.5 to 1 part of tea polyphenols to 50 to 70 parts of 40 to 70 wt% ethanol aqueous solution; ultrasonically disperse, and dropwise add 0.4 to 0.6 mol / L phosphoric acid to adjust the pH of the mixture; The mixture was stirred and reacted at 40-60° C. for 5-15 hours, centrifuged and washed with anhydrous ethanol for 1-3 times, and dried at 40-60° C. for 4-10 hours to obtain an additive; S3, uniformly mixing the prepared modifier and additive to obtain a functional agent.

7. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 6, characterized in that: The pH of the mixture is adjusted to 5-6.

8. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 6, characterized in that: The power of the ultrasonic dispersion is independently 150-300 W, the frequency is independently 20-60 kHz, and the time is independently 20-50 minutes.

9. The method for preparing the leather composite material capable of sustainably releasing negative ions as claimed in claim 6, characterized in that: The modifier and the additive are mixed evenly in a weight ratio of 1-3:0.5-1.

10. A leather composite material capable of continuously releasing negative ions, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A denitrification catalyst and its preparation method

    CN107899588B

  • PVC artificial leather capable of efficiently releasing negative ions and preparation method thereof

    CN105696360A

  • Ecological anion releasing artificial leather and preparation method thereof

    CN106192443A

  • Antibacterial crease-resist PVC artificial leather and preparation method thereof

    CN106192444A

  • Nanometer artificial leather and manufacturing method therefor

    WO2017012240A1